Intraoperative Infusion of Magnesium Sulphate does not Reduce Laryngospasm and Agitation during Emergence from Anaesthesia in Children - Khatiwada, S.; Pokharel, K.; Subedi, A. (Kathmandu University Medical Journal, 2020)
Background Laryngospasm and agitation during emergence from general anaesthesia are frequent in children. Magnesium sulphate may have the potential of reducing both of these adverse events. In addition, magnesium has analgesic and anaesthetic properties. Objective To find out the effectiveness of magnesium sulphate in reducing the occurrence of emergence laryngospasm and agitation and other adverse events if any in children. Method Randomized, placebo controlled study was conducted at a tertiary care hospital in 132 children, aged 3-12 years undergoing general anaesthesia for hernia and hydrocele surgery. Children with American Society of Anaesthesiologist Physical Status > II were excluded. After insertion of laryngeal mask airway, 20 ml of either magnesium sulphate 15 mg/kg (Group M) or normal saline (Group N) was infused at the rate of 1 ml/min. The severity of laryngospasm and agitation was assessed. We also noted other adverse events, if occurred. Result Laryngospasm occurred in 7(10.6%) patients of group M and in 10(15.1%) patients of group N(p=0.40). While 14(10.6%) patients developed laryngospasm immediately after removal of LMA, only 3(2.2%) patients developed it in the post anaesthetic care unit. Two (3.0%) patients of group M and four patients (6.0%) of group N were agitated (p=0.40). Three (4.5%) patients of group M and 14(21.2%) patients of group N coughed during emergence (p=0.004). Conclusion Intraoperative infusion of 15 mg/kg magnesium sulphate, does not reduce the occurrence of emergence laryngospasm and agitation in children. However, it significantly reduce emergence cough.